Process linkages in large watersheds: connecting tributary erosion to downstream channel change and floodplain forest establishment in the Yampa and Green River Basin - Kemper, John Trusal, author; Rathburn, Sara, advisor; Friedman, Jonathan, committee member; Wohl, Ellen, committee member; Leisz, Stephen, committee member; Redmond, Miranda, committee member (Colorado State University. Libraries, 2022)
It is well-understood that the physical state of a river is a combination and culmination of present processes and past trajectories. Similarly, conceptualizations of fluvial connection hold that various aspects of a given river reach – ecologic, geomorphic, hydrologic – do not operate in isolation, but rather as components within a linked system, both influencing and influenced by upstream and downstream conditions. To expand understanding of the river system as an intrinsically linked network of both process and form, here I establish connections between the processes of historical tributary erosion and distal downstream channel migration and floodplain forest establishment in the Yampa and Green River Basin. I then additionally summarize the extensive body of literature concerning the geomorphic response to sediment supply increases in low-gradient, alluvial rivers to further emphasize that the translation of sediment through the landscape can catalyze myriad responses that manifest across a continuum of scales. Concentrating initially on the investigation of historical erosion, examination of historical documents and aerial photos suggests that three key sediment contributing tributaries of the Yampa River – Sand Creek, Muddy Creek, and Sand Wash – underwent substantial historical erosion from 1880-1940. Using field investigation to determine historical channel location and field surveys of present-day dimensions, I then calculate that historical arroyo incision within the latter two tributary watersheds injected 30 x 106 tons of sediment into the mainstem Little Snake and Yampa Rivers during this time. Taking present-day annual sediment loads as an approximate background for the pre-erosion sediment regime, this represented a sizable increase in the sediment load of the Yampa River during the period of historical erosion. Moving downstream, results of dendrochronologic analysis of tree cores from three separate forest locations – Deerlodge Park on the Yampa River, Island Park and Tuxedo Bottom on the Green River – indicate that major portions of these forests established during the same time period of elevated historical erosion. Moreover, channel change analysis suggests that the channel at this time was relatively more dynamic than it has been since, and the area of forest dating to the historical period is much greater than can be explained by high flows alone. Viewed collectively, these findings suggest tributary erosion played a vital role in successful downstream forest establishment. Additional sediment fingerprinting analysis further supports this process link between geomorphic and ecologic process. Using sediment samples taken at the rooting surface of the cottonwood forest in Deerlodge Park, geochemical analysis indicates that the majority of this sediment was sourced from those tributaries – Muddy Creek and Sand Wash – that were undergoing enhanced erosion via arroyo incision during the historical period. Overall, the temporal overlap between the timing of historical tributary erosion and the establishment of substantial portions of downstream floodplain forest, in conjunction with the fact that floodplain sediment is dominantly sourced from watersheds that experienced enhanced historical erosion, together indicates a demonstrable link between the geomorphic process of historical erosion and the ecologic process of downstream floodplain forest establishment. From a summary of existing studies concerning the geomorphic adjustment of low-gradient, alluvial rivers to increased sediment supply, it is additionally clear that tributary erosion that injects substantial amounts of sediment into a river system can result in the requisite channel change necessary for successful forest establishment. The fluvial system is thus best understood as not just a physically coupled network, but a collectively connected web of processes that together regulate and are regulated by one another. Such an understanding emphasizes that management of large watersheds must be holistic and undertaken at the basin scale in order to ensure that vital riverine ecosystems endure.
Keywords: dendrochronology; Green River; Yampa River; erosion; channel change; sediment fingerprinting